Er:YAG and adhesion in conservative dentistry : clinical overview - Fornaini, Carlo (Japan Medical Laser Laboratory, 2013)
The notion of utilizing laser technology in conservative dentistry was proposed in 1990 by Hibst and Keller, who introduced the possibility of using an Er:YAG laser as alternative to conventional instruments such as the turbine and micro-motor. In subsequent years a continuing effort has been made by clinicians, researchers and commercial companies to improve the technology. The aim of this clinical study is to demonstrate, by the description of different clinical cases, the possibilities and the advantages of using Er:YAG lasers in conservative dentistry and to show that better results may be achieved in terms of stronger adhesion, less invasiveness, reduced pain as well as greater comfort and satisfaction of patients.